Relationship Between Item and Source Memory: Explanation of Connection-Strength Model - Guo, Junjun; Shubeck, Keith; Hu, Xiangen (Frontiers in Psychology, 2021)
The controversy in the relationship between item and source memory is one focus of episodic memory. Some researches show the trade-off between item and source memory; some show the consistency between item and source memory; and others show the independence between item and source memory. Our review tries to point out connection-strength model implying the different strength of item-source connections’ important role in the relationship between item and source memory to explain the disputation.